Phaya: The Role and Communication on Social Media Area - Saengkaew, Chalermpol; Buarabha, Homhuan; Sriruksa, Kittisan (International Journal of Membrane Science and Technology, 2023)
This research article was part of the Phaya research study on the roles and communication in social media space, with the aims of studying the role and communication of the Phaya on social media by focusing on 1) Facebook, 2) YouTube, and 3) Instagram. Methods of documentary and field data collection were utilized. Surveys, observational forms, interviews, and focus groups were the instruments used in this study. The 30 participants were from knowledge groups, practitioner groups, and corresponding groups. Photographs were used to provide descriptive data for the analysis. The results showed that the Phaya's role and communication on the social media space were carried out in four processes: 1) continuing processes and outcomes of transmitting both direct and implicit meanings of the Phaya on the social space. As a questioner, the researchers discovered a method of asking philosophical questions and questions about social events, 2) the continuing process and outcomes of direct and meaningful contact, and the implications of the Phaya that appears on the social space as a claimant. Consequently, the process of advocating for justice, love, unity, and becoming the Isaan (Thai's northern dialect) began. Social capital was developed as a powerful "media" of the Isaanism as a result of communication, and 3) the ongoing process and the result of communication, both in direct and indirect meaning. As a guide, there was a process of moral guidance, socialization, and local cultural education. As a result of communication, there was identity creation, awareness, and life value creation, along with maintaining the norms of the Isaan society, and 4) continuous processes and communication outcomes, both directly and indirectly, as well as the Phaya implications that surface on the sympathetic space of being speak and explain. Thus, the process of presenting the social and cultural aspects of the northeastern area, in which the content was related to both past and contemporary settings, appears straightforward, modern, and appropriate. The monologue resulted in the comprehension of the essence and awareness of the issue. And there was a learning experience in your spare time, in which the knowledge gained may be utilized to conserve, distribute, and further produce acceptable the Phaya literature for the future maturity.